1992
DOI: 10.1002/1098-2337(1992)18:3<219::aid-ab2480180305>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of aggressive behavior

Abstract: A multiple factor approach was used to test additive and multiplicative models as well as to isolate a best predictive model of physical aggression. The variables of aggressive learning history, provocation, sex of target, sex of subject, sex‐role orientation, and aggressive tendencies were selected. Eighty‐three males and 117 females participated in the experimental session. Multiple regression analyses indicated that multiple predictor models were able to account for significantly more variance than were sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
49
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 28 publications
4
49
0
Order By: Relevance
“…For example, Pool et al [2007] used electrical shock to demonstrate that hypermasculine men report having higher pain tolerance, and actually tolerate more electrical stimulation than women and men who endorsed low levels of masculinity. 2 Similarly, Hammock and Richardson [1992] used an electric shock aggression paradigm to demonstrate that masculinity is a better predictor of aggression than gender alone. Kogut et al [1992] found that women who endorse more masculine traits are more aggressive than low masculine endorsing women.…”
mentioning
confidence: 99%
“…For example, Pool et al [2007] used electrical shock to demonstrate that hypermasculine men report having higher pain tolerance, and actually tolerate more electrical stimulation than women and men who endorsed low levels of masculinity. 2 Similarly, Hammock and Richardson [1992] used an electric shock aggression paradigm to demonstrate that masculinity is a better predictor of aggression than gender alone. Kogut et al [1992] found that women who endorse more masculine traits are more aggressive than low masculine endorsing women.…”
mentioning
confidence: 99%
“…The conceptualization of femininity and masculinity as independent dimensions also suggests it would be valuable to their relative contribution to behaviors, such as aggression, which are strongly associated with gender roles. Several studies have shown that high masculinity in sex role orientation predicts aggression, in men as well as women [e.g., Hammock and Richardson, 1992;Jenkins and Aube, 2002]. While evidence for a link between masculinity in the form of macho personality and aggressive driving has been established for men [Krahe´and Fenske, 2002], there is no evidence to date to explore the role of women's masculinity.…”
mentioning
confidence: 99%
“…Moreover, there is a significant amount of research looking at sex differences in different types of aggressive behavior [e.g., [6][7][8][9][10][11][12][13][14][15]. However, differences in aggressiveness between men and women are often small and inconsistent [16][17][18]. It has often been suggested that males are in general more physically aggressive than females [18][19][20][21].…”
Section: Introductionmentioning
confidence: 71%